VOLODYMYR GAVRYLOVYCH BONDARCHUK – DEVELOPER OF UKRAINIAN SCIENCE - Mykhailov, V.; Shevchuk, V.; Ivanik, O.; Yanchenko, V.; Yanchenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article explores scientific, administrative, and public activity of V.G. Bondarchuk – prominent Ukrainian scientist, renowned geologist, rector of Taras Shevchenko State University of Kyiv in 1944–1951, the most strenuous period in the University operation. It highlights his contribution to Ukrainian geological science during the post war period to promote its further development and advancement.